Changes in knee adduction moment wearing a variable‐stiffness shoe correlate with changes in pain and mechanically stimulated cartilage oligomeric matrix levels. Issue 3 (22nd June 2020) - Erhart‐Hledik, Jennifer C.; Mahtani, Gordhan B.; Asay, Jessica L.; Migliore, Eleonora; Nguyen, Michelle M.; Andriacchi, Thomas P.; Chu, Constance R.
Abstract: This study aimed to determine if changes in knee adduction moment (KAM) after 6 months of variable‐stiffness shoe wear are associated with changes in symptoms or serum levels of cartilage oligomeric matrix protein (COMP) following a mechanical stimulus in subjects with medial knee osteoarthritis (OA). Twenty‐five subjects were enrolled in the study and assigned a variable‐stiffness shoe, and 19 subjects completed the 6‐month follow‐up. At baseline and follow‐up subjects underwent gait analysis in control and variable‐stiffness shoes, completed Western Ontario and McMaster Universities (WOMAC) questionnaires, and serum COMP concentrations were measured immediately before, 3.5 and 5.5 hours after a 30‐minute walking activity. Relationships between changes in KAM (first peak and impulse) and changes in (a) COMP levels in response to the 30‐minute walking activity and (b) WOMAC scores from baseline to 6‐month follow‐up were assessed by Pearson correlation coefficients. Changes in first peak KAM were associated with changes in COMP levels 5.5 hours postactivity from baseline to follow‐up ( R = .564, P = .045). Subjects with greater reductions in KAM had larger decreases in COMP (expressed as a percent of preactivity levels) at follow‐up. Subjects with greater reductions in KAM impulse had significantly greater improvements in WOMAC Pain ( R = −.56, P = .015) and Function ( R = −.52, P = .028) scores at follow‐up. The study results demonstrated the magnitude of reduction in the KAM wearing a variable‐stiffness shoe is associated with decreases in mechanically stimulated COMP levels and pain/function. This work suggests that interactions between COMP and joint loading during walking should be further investigated in future studies of treatment outcomes in OA.